Feminization of Agriculture : Trends and Driving Forces - Lastarria-Cornhiel, Susana (Washington, DC: World Bank, 2012)
Women have broadened and deepened their involvement in agricultural production over the last few decades as they increasingly shoulder the responsibility for household survival and respond to economic opportunities in commercial agriculture. This paper will describe how women have increased their labor in two types of agricultural production--smallholder production and agro-export agriculture--and the economic and socio-cultural forces that are driving this trend.